Electrochemical Estrogen Receptor α based Biosensor for Label‐Free Detection of Estradiol. Issue 7 (14th June 2013) - Guo, Zhenzhong; Zine, Nadia; Balaguer, Patrick; Zhang, Aidong; Namour, Philippe; Lagarde, Florence; Jaffrezic‐Renault, Nicole
Abstract We describe a new electrochemical biosensor based on estrogen receptor α (ER‐α) for label‐free detection of 17β‐estradiol, a model of endocrine‐disrupting compounds. ER‐α is coupled onto the gold electrode through its 6‐His tag and NTA‐copper complex. After interaction of estradiol with ER‐α, the biosensor presents a well‐defined peak at +500 mV due to estradiol oxidation (E17 peak). The linear range of detection is from 1 fM to 1 nM and the detection limit is 1 fM. Good selectivity was obtained for interfering substances at nanomolar level, for concentration of E17 up to 0.1 pM. The E17 was detected in hospital effluents.